Nádrž, kvapalina a podložie - Kotrasová, K. (Видавництво Національного університету «Львівська політехніка», 2007)
This article contains description of some methods for solution of response of vertical rectangular containment with fluid on the soil, which is subject to horizontal seismic loads. First part of the present article consideres impulsive and convective components of the fluid with various dynamic behaviours. The special method of calculation of response of containment is described in further part of the paper. Computer-program Cosmos/M was used.